AN INNOVATIVE EUROPEAN SPORTS TUTORSHIP MODEL (ESTPORT) FOR THE DUAL CAREER OF STUDENT-ATHLETES - Sánchez-Pato, Antonio; García-Roca, Juan Alfonso; Isidori, Emanuele; Leiva-Arcas, Alejandro (Revista da ALESDE, 2021)
The Dual Career of Student-Athletes is a topic of great interest in Europe, and the European Commission supports projects to implement measures that promote and stimulate this career. Within the European Dual Career ESTPORT project, two sports tutoring models were analyzed (UCAM Tutorship Model and DUCASTUN Model) in two different countries (Spain and Italy). In 2016, the UCAM model of sports tutoring was used to tutoring 188 students. They were granted a scholarship and assisted by an individual tutor. The model and the system which has developed from it was evaluated. That provided essential pieces of information on sports life, academic life and sports tutoring. The DUCASTUN model of the University of Rome “Foro Italico”, was implemented with 18 student-athletes and evaluated through the ESTPORT project, emphasizing the use of Web 2.0 technology as an essential element to achieving effective sports tutoring.